Some Comments on Work Practices at the Ruler’s Chancellery during Its Provisional Administration by Ivan Hornostay in 1540–1546 (According to Data from Lithuanian Metrica Books No. 24, 28 and 231 (Court Case Book No. 12)) - Dubonis, Artūras (Vilnius University Open Series, 2024)
This article presents an analysis of three Lithuanian Metrica books, formed in around 1540–1544, namely – books No. 24, 28 and Court Case Book No. 12, looking at their purpose and interrelativity, and the value of their information as historical sources. The author of this article found some source-research related confusion in these books, due to which historians studying this period may inadvertently incorporate a degree of undesirable errors in their work. The above-mentioned books of the Lithuanian Metrica were formed at a time when the state treasurer and grand ducal chancellery clerk Ivan Hornostay was serving as the head of the chancellery of the Grand Duchy of Lithuania following the death of Chancellor Albertas Goštautas (December, 1539).In presenting the work practices executed by the chancellery of the Grand Duchy of Lithuania in 1540–1544, the analysis of the interrelation of Lithuanian Metrica books No. 24, 28 and Court Case Book No. 12 and the “movement” of the documents they contained allowed me to arrive at several observations. The chancellery’s work practices were found to indicate the considered redaction of texts, whereby seeking to give them the attributes of an official document, changes and additions to the regular formulated language would be made. Hornostay is deemed the most important official-bureaucrat in this activity, having direct control over the clerks in the chancellery of King and Grand Duke Sigismund the Old and indirectly – of his wife, Queen Bona, and son Sigismund Augustus, as official documents issued in the ruler’s name could only be stamped and entered into the chartulary (chartularium) kept by Marcin Tur with Hornostay’s knowledge. The noticeably significant impact of Hornostay on the ruler made it possible to influence the latter’s official decisions regarding various matters in the internal life of the state. Hornostay was the most important chancellery official not only in 1540–1544 as the executor of the chancellor’s office, but earlier as well. The bureaucratic purpose of these three analysed books of the Lithuanian Metrica may be explained differently than by grouping them into Books of Inscriptions (No. 24 and 28) and a Court Case Book (Court Case Book No. 12), as the modern period historiographic scheme of 1887 devised by Stanisław Ptaszycki dictates. Rather, we should consider Lithuanian Metrica Book No. 24 as the chartulary Book of Inscriptions containing the ruler’s official documents, whereas Book No. 28 and Court Case Book No. 12 were formed from series of clerks’ files, in which the majority of documents were not yet officially authorised – these were drafts, concepts (minutes), preliminary papers, court case protocols, the ruler’s provisional resolutions and alike. In both of the latter books of the Lithuanian Metrica we find the drafts of documents of various content, even though court case documents dominate in one book, while the other had mostly grants (endowments), records of provenance, and alike. This kind of record-keeping was found to lack consistency in the manner that documents were ordered, the documents themselves having been entered haphazardly.This research of three books of the Lithuanian Metrica by no means explains all of the aspects of the activities of the chancellery of the Grand Duchy of Lithuania from that time, but only accounts for several years after the death of Albertas Goštautas. These aspects are related to the same changes to document content that were made during the progression from a draft to its official version.
Keywords: Grand Duchy of Lithuania; Lithuanian Metrica; Chancellery of the grand duke of Lithuania; Ivan Hornostay